INDUCTION AND STIMULATION LABOR WITH PROSTAGLANDIN F2-ALPHA - Huamán, Moisés (2015)
Labor induction was performed on 40 women using prostaglandin F2-Allfa in isotonic sodium chloride solution in infusion; was monitored at all with external monitoring and in half, infusion pump was used. The indications for induction were: premature rupture of membranes hypertensive disease of pregnancy (20%) and prolonged pregnancy (10%). The average age of patients was 29.7 years, 60% were primigestos, 80% were between 36 and 40 weeks and the remainder over 40 weeks. Bishop all had greater than 4. The length of dilation, in primiqestas, was 6.4 hours on average 4.3 variations {7.1 hours); in multiparous was 5.3 hours (range 3.7 to 6.8 hours). The doses used ranged from 3 to 15 ug / 1 '(6.9 ug / 1' average). There were no complications in uterine activity or fetal heartbeats. A case of mild nausea and vomiting was observed. The delivery was eutocic in 92% of cases, there was one cesarean section and 2 cases of failed induction (5%). The birth was normal. The average weight of newborns was 3193 gr. APGAR was good and the 3 '100% of RN. In another group of 30 pregnant women with dysfunctional labor, it was possible to correct the uterine contractions with average doses of 5 ug / 1 ', without maternal or fetal complications.